124 AN INTERDISCIPLINARY PREHABILITATION PILOT FOR FRAIL ADULTS UNDERGOING ELECTIVE ANTERIOR RESECTION AND HARTMANN'S REVERSAL SURGERIES IN AN IRISH ACUTE HOSPITAL. (25th October 2022) - Treanor, C; Smith, J; McCabe, M
Abstract: Background: Frailty affects 21.5% of individuals aged 65 and over in Ireland (TILDA, 2017).Timely interventions can limit or reverse the impacts of frailty. Local HIPE data from 2016-2020 highlighted correlations between increased average Length of Stay (aLOS) and median age (>65 years) for those undergoing elective Anterior Resections and Hartmann's reversal surgeries. Prehabilitation aims to identify and manage modifiable risk factors that may impact on LOS, as well as optimise patients' resilience and physiological reserves to reduce postoperative complications. Modifiable factors include pre-operative function, co-morbidities and post-operative delirium. In the Republic of Ireland, surgical interdisciplinary Prehabilitation services exist only in one hospital. Methods: An interdisciplinary prehabilitation pilot for individuals undergoing elective colorectal surgeries was developed. Patients are referred from surgical clinics to Physiotherapy, Occupational Therapy or Dietitian preoperatively. Interventions include respiratory optimisation, exercise prescription, discharge planning, equipment provision and pre-operative nutritional reviews. Results: Three elective patients have completed the first phase of the pilot. Two underwent anterior resections and one underwent a Hartmann's reversal. The LOS for each individual was 4 days respectively, 4 days under the KPIs. Patients received virtual assessment and individualised interventions including an interdisciplinary educational booklet. Interventions included: exercise programmes, nutritional support, discharge planning discussion and equipment as indicated. No post-operative complications were identified and no interim beds or home supports were required. Qualitative feedback surveys were completed by all participants. Subjective feedback from patients has been overwhelmingly positive. Conclusion: Patients report feeling physically and psychologically better prepared for surgery with better knowledge of post-operative expectations. Patients are more proactive in their postoperative recovery meaning they can return home sooner. This pilot enhances evidence-based ERAS practice, improving the quality and safety of patients journey. Participants also had a 12 day cumulative reduction in aLOS with financial savings of €12000.